Alkyl‐Chain‐Regulated Charge Transfer in Fluorescent Inorganic CsPbBr3 Perovskite Solar Cells. (28th January 2020) - Duan, Jialong; Wang, Yudi; Yang, Xiya; Tang, Qunwei
Abstract: Improved charge extraction and wide spectral absorption promote power conversion efficiency of perovskite solar cells (PSCs). The state‐of‐the‐art carbon‐based CsPbBr3 PSCs have an inferior power output capacity because of the large optical band gap of the perovskite film and the high energy barrier at perovskite/carbon interface. Herein, we use alkyl‐chain regulated quantum dots as hole‐conductors to reduce charge recombination. By precisely controlling alkyl‐chain length of ligands, a balance between the surface dipole induced charge coulomb repulsive force and quantum tunneling distance is achieved to maximize charge extraction. A fluorescent carbon electrode is used as a cathode to harvest the unabsorbed incident light and to emit fluorescent light at 516 nm for re‐absorption by the perovskite film. The optimized PSC free of encapsulation achieves a maximum power conversion efficiency up to 10.85 % with nearly unchanged photovoltaic performances under 80 %RH, 80 °C, or light irradiation in air. Abstract : An der langen Leine : Die Regulierung der Alkyl‐Kettenlänge von Quantenpunkten, die an anorganische CsPbBr3 ‐Perowskite gebunden sind, maximiert die Ladungsextraktion und den Transfer an der Perowskit/Kohlenstoff‐Grenzfläche. Eine optimierte anorganische CsPbBr3 ‐Perowskit‐Solarzelle (PSC) mit C12 ‐Alkylketten‐QDs zeigt einen Wirkungsgrad von bis zu 10.85 %.